METHODICAL ASPECTS OF PEDAGOGICAL TECHNOLOGY OF TEACHING OF SCHOOLBOYS IN THE PROCESS OF STUDY OF ARTISTIC GRAPHIC ARTS - Ya.M. Serdotetska (Academy of Cognitive and Natural Sciences, 2022)
In the article is regarded the questions of the methodic pedagogical technology of learning students the based of art graphic.